How Birds During Migration Maintain (Oxidative) Balance - McWilliams, Scott; Carter, Wales; Cooper-Mullin, Clara; DeMoranville, Kristen; Frawley, Abigail; Pierce, Barbara; Skrip, Megan (Frontiers in Ecology and Evolution, 2021)
Animals dynamically adjust their physiology and behavior to survive in changing environments, and seasonal migration is one life stage that demonstrates these dynamic adjustments. As birds migrate between breeding and wintering areas, they incur physiological demands that challenge their antioxidant system. Migrating birds presumably respond to these oxidative challenges by up-regulating protective endogenous systems or accumulating dietary antioxidants at stopover sites, although our understanding of the pre-migration preparations and mid-migration responses of birds to such oxidative challenges is as yet incomplete. Here we review evidence from field and captive-bird studies that address the following questions: (1) Do migratory birds build antioxidant capacity as they build fat stores in preparation for long flights? (2) Is oxidative damage an inevitable consequence of oxidative challenges such as flight, and, if so, how is the extent of damage affected by factors such as the response of the antioxidant system, the level of energetic challenge, and the availability of dietary antioxidants? (3) Do migratory birds ‘recover’ from the oxidative damage accrued during long-duration flights, and, if so, does the pace of this rebalancing of oxidative status depend on the quality of the stopover site? The answer to all these questions is a qualified ‘yes’ although ecological factors (e.g., diet and habitat quality, geographic barriers to migration, weather) affect how the antioxidant system responds. Furthermore, the pace of this dynamic physiological response remains an open question, despite its potential importance for shaping outcomes on timescales ranging from single flights to migratory journeys. In sum, the antioxidant system of birds during migration is impressively dynamic and responsive to environmental conditions, and thus provides ample opportunities to study how the physiology of migratory birds responds to a changing and challenging world.